Taxonomic And Ecological Studies Of Stoneflies (Insecta: Plecoptera) In Selected Rivers At Royal Belum State Park, Perak, Malaysia - Adnan, Wan Nur Asiah Wan Mohd (2012)
Taxonomic study of stoneflies (Insecta:Plecoptera) was carried out by examining variations of ♂ and ♀ genitalia, morphology of their nymphs, size and shape of eggs and structures on egg chorion. Specimens were collected by bucket trapping (adult) and kick sampling technique (nymph) from rivers of Royal Belum State Park (RSBP); Kejar, Mes, Tan Hain and Ruok. A total of 98 (54♂, 44♀) adults and most of the 8132 nymphs were identified to the species level. A new species,Etrocorema belumensis was discovered and named after the RBSP. Several other species such as Etrocorema nigrogeniculatum, Kamimuria trang, Neoperla fallax, Neoperla hamata, Neoperla asperata, Phanoperla malayana, Cryptoperla fraterna were new records for this catchment.